2023
DOI: 10.2147/rmhp.s396495
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Telemonitoring in Health Care: Facilitators and Barriers for Using eHealth for Older Adults with Chronic Conditions

Abstract: Purpose The retrospective study used a hybrid design aimed to a) describe the implementation process of telemonitoring from stakeholders’ perspectives and b) identify facilitators and barriers perceived by the care team. Patients and Methods Qualitative interview data were analyzed using manifest inductive qualitative content analysis to describe what was perceived as barriers and what facilitated the implementation. Participating healthcare professionals recruited from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Telemonitoring has been more frequently studied in older adults, but mainly in ambulatory settings and focused on chronic illnesses [ 48 50 ]. In this study, the intervention will be evaluated in acutely ill older patients admitted to a Geriatric ED and trained in the use of walking aids.…”
Section: Discussionmentioning
confidence: 99%
“…Telemonitoring has been more frequently studied in older adults, but mainly in ambulatory settings and focused on chronic illnesses [ 48 50 ]. In this study, the intervention will be evaluated in acutely ill older patients admitted to a Geriatric ED and trained in the use of walking aids.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study revealed that nurses with higher job titles, higher educational levels, and higher monthly incomes expressed a significant demand for IHC care compared with their counterparts with lower job titles, lower educational levels, and lower monthly incomes. Because most of the people with higher titles and more education have longer working hours, extensive work experience, and are able to calmly and stably handle various unexpected events that may arise [ 17 ], they have given sufficient consideration to their demands, such as the requirements for improving the qualifications of nurses providing IHC services and developing complete regulations and laws [ 37 ]. Consistently, previous studies reported that professional title, educational level, and mortgage or car loan were associated with nurses’ demand for IHC services [ 13 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, we can use some technologies in the IHC services. The study by Liljeroos and Arkkukangas [ 37 ] indicated that suitable adoption of devices and technologies is important in facilitating care delivery. Adequate patient and caregiver training and easy-to-use devices, such as wearables for remote vital sign monitoring, have been shown to result in greater satisfaction, improved ability to use the device, and better overall functioning [ 37 ], which is related to the technology areas mentioned in the NASSS framework [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, others underpin the patients' concerns regarding the impact of TM on physicians' attentiveness, while doctors state that such systems might provide novel insights into patients' living circumstances [80]. Additional concerns and obstacles are raised when eHealth is implemented in older patients [84], such as insufficient technical literacy and hesitancy in using digital tools, with apprehensions regarding privacy and security. Of note, infrequent face-to-face visits might enhance loneliness and depression feelings in this age group [85,86].…”
Section: Addressing Concerns and Barriers To Telemonitoring Implement...mentioning
confidence: 99%